Development of Learning Model of Youtube-Based Learning in Light Vehicle Electricity Maintenance Subject - Saputra, Indra; Muchlas, Muchlas; Achsan, Bambang Nor (Journal of Vocational Education Studies, 2020)
This study aims to develop a learning model of Youtube-Based Learning to facilitate the learning habits of digital-age students. This research used the research and development method. The research steps were analysis of potential and problems, data collection, product design, design validation, design revisions, limited implementation test, revisions, implementation tests, revisions, and mass production. Subject research was the students of class XI of Light Vehicle Engineering at SMK Muhammadiyah 1 Playen. Research data collection used closed questionnaire, open questionnaire, and integrated with interviews and observations. The data analysis technique used the effect size test. The results showed that the validity of Youtube-Based Learning included in the very feasible category to apply. The contribution given by Youtube-Based Learning on student learning outcomes was 58%. Other results showed that students and teachers gave positive responses to the learning model of Youtube-Based Learning.